The Effect Of Mudharabah Financing Income To Profitability (ROA) At PT. Bank Muamalat Indonesia Tbk. Periode 2011-2016 - Sjamsuddin Ak Antuli (IAIN Manado, 2018)
AbstractOne of funds allocations in Islamic banking is mudharabah financing. It will generate profits from the calculation for the results. The profit will be shared between the bank and its managing customers. The rate of return on capital can measure the level in profitability of a bank by comparing its profit and capital. The purpose of this study was to examine the effect of mudharabah financing income on the profitability of PT. Bank Muamalat Indonesia Tbk. The method was used quantitative descriptive with analysis technique of simple regression analysis using SPSS version 21. The results showed that simultaneously the p-value value is 0,000 and smaller than the level of significant that is 0.05 which means mudharabah financing income affect profitability simultaneously. Partially, (T test) shows that the value of T count = 4.670> 1.711 T table while the significance value is 0.000 where this number is smaller than 0.05. From the calculation results obtained by the coefficient, b = 0.115 is positive, this means that every time the mudharabah financing income increases by one (1), the average profitability (ROA) will increase by 0.115. This means that mudharabah income has a positive and significant effect on the ROA level partially. Keywords : Mudharabah, Profitability, Return On Assset (ROA)